Internal jugular vein thrombosis in Behcet’s disease: a rare complication - Bilici, Muhammet (BMJ Publishing Group, 2014)
Behcet’s disease (BD) is a systemic inflammatory disorder characterised by oral/genital ulcers, ocular lesions, and gastrointestinal, musculoskeletal, neurological and major vessel involvements. Venous manifestations are more common than arterial involvements. In this case report, we present a patient with internal jugular vein thrombosis, which is a very rare complication of BD.